Enhancing biodegradation of crude oil in soil using fertilizer and empty fruit bunch of oil palm - Ainon Hamzah,; Siti Nursyazana Md Salleh,; Sukiman Sarmani, (Universiti Kebangsaan Malaysia, 2014)
Bioremediation of crude oil using biostimulation and/or bioaugmentation was done by simulation study in the green house under uncontrolled environment temperature. In this study, the soil with indigenous microbes was spiked with Tapis crude oil at 200 g/kg. The microbial density of the amended soils was augmented by addition of fresh inoculum of microbial consortium which consist of Pseudomonas aeruginosa UKMP-14T, Acinetobacter baumannii UKMP-12T and seed culture two strains of fungi, Trichoderma virens UKMP-1M and Trichoderma virens UKMP-2M at ratio 1:1:1:1 (v/w). The amendment soil was added with 20% (v/w) of standardize consortium inoculum, 20% (w/w) of dried empty fruit bunch (EFB) and the effect of EFB was compared with 0.7% commercial fertilizer (v/w) which contain NPK (8:8:1). Soil with indigenous microbes was used as a control. Results showed total petroleum hydrocarbon (TPH) degradation for treatment added with NPK fertilizer was 70.36%, addition with EFB bulking agent 68.86% and addition of both NPK and EFB was 100% at day 30 of incubation. The control plot, 62% of   TPH degradation was achieved after 30 days incubation.